Lumbar intervertebral disk degeneration in athletes - Hangai, M.; Kaneoka, K.; Hinotsu, S.; Shimizu, K.; Okubo, Y.; Miyakawa, S.; Mukai, N.; Sakane, M.; Ochiai, N. (The American Journal of Sports Medicine, 2009)
Background Several studies have reported that physical loading related to competitive sports activities is associated with lumbar intervertebral disk degeneration. However, the association between types of sports activities and disk degeneration has not been clarified.